HAMBATAN PEMANFAATAN JAMINAN PERSALINAN (JAMPERSAL) DI PUSKESMAS WILAYAH KABUPATEN BONE BOLANGO PROVINSI GORONTALO - , ROOS PANAI; , Dr. drg. Julita Hendratini, M.Kes ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Jampersal (Delivery Insurance) Program in Bone Bolango regency had been implemented since 2011. Deliveries in health facilities increased but the number of non delivery of health facilities is still quite high at 23.7 %, maternal mortality increased threefold. This describes the problems in the implementation of Jampersal (delivery insurance) that causes society had not fully utilize Jampersal. Objective: To determine the factors influenced the barriers of Jampersal utilization in Bone Bolango regency. Methods: The qualitative research with case study design. The variables of this study were: Jampersal, mother's knowledge, family support, access, and quality of service. The research subjects were 25 informants, namely maternal who did not utilize Jampersal, the manager of Jampersal program and midwives. The sample determination was using purposive sampling technique. Data analysis was carried out systematically from the transcript until analysis. Results: The public did not utilize Jampersal in Bolango Bone regency due to lack of socialization and occur in women with a low educational level. The lack of mothersâ knowledge about Jampersal, symptoms and signs of labor and safe delivery caused delays in making decision of maternity in health facilities. The big difference in making decision in a remote area is determined by the parents while in the regular area is determined by the husband. Delivery is usually takes place at parentsâ home and birth attendants have a family relationship. Poskesdes not be utilized for service delivery as unfit for human habitation and not fitted with equipments. The less competent midwife, relatively young age, less experience and most of them do not live in the village, as well as the customs and habits of the people were important factors affecting women giving birth at home. Conclusion: Barriers of Jampersal utilization due to lack of socialization, customs and habits of the community, the availability of service delivery in the form of personnel readiness and delivery care facilities, as well as the complexity of the administrative claimants Jampersal funds.